Pratique des activités d’orientation-conseil et projet professionnel de l’élève au Cameroun - Rodrigue Mbwassak (Éducation et Socialisation)
Nowadays, in view of the many issues and hopes it raises, guidance counselling through the vocational project is that training interface which favours academic success and the preparation of the pupil for a future professional career. This research poses the problem of guidance counsellors accompanying students in the co-construction of their professional projects preparing them for a secure professional integration, if we refer to the difficulties of choice of training and socio-professional integration experienced by graduates nowadays. To this end, a questionnaire was administered to a sample of 628 students in the final year of secondary school in the city of Bertoua. The testing of four hypotheses by the multiple logistic regression test made it possible to verify that the use by guidance counsellors of their main activities (training sessions, counselling, applied research and psycho-technical testing) favours the accompaniment of students in the construction of their professional projects.